Mn vanadate nanoneedles for visible light photocatalytic activity of rhodamine B. Issue 1 (6th February 2015) - Lin, N.; Pei, L. Z.; Yu, H. Y.; Wei, T.
Abstract : Mn vanadate nanoneedles have been successfully prepared via a simple hydrothermal process using sodium vanadate and Mn chloride as the raw materials, sodium dodecyl sulfate (SDS) as the surfactant. The samples are characterised by X-ray diffraction (XRD) and scanning electron microscopy (SEM). The Mn vanadate nanoneedles are composed of orthorhombic MnV2 O5 phase and have the diameter of the tips and length of about 50 nm and 10 µm, respectively. The preparation parameters including SDS concentration, hydrothermal temperature and duration time have important roles in the formation of Mn vanadate nanoneedles. The photocatalytic activities of the Mn vanadate nanoneedles are assessed based on the degradation of rhodamine B (RB) in aqueous solution under solar light irradiation. The roles of irradiation time, dosage of the Mn vanadate nanoneedles and initial concentration of RB solution on the photocatalytic degradation have been investigated. The RB degradation ratio reaches 97.41wt% using 10 mg Mn vanadate nanoneedles in 10 ml 10 mg/l RB solution under solar light irradiation. The Mn vanadate nanoneedles exhibit good photocatalytic performance for the degradation of organic pollutants.